Entre les rites, le rythme et la routine. Les fragments du monde de Hélène Rioux - Figas, Ewa (Romanica Silesiana)
The three novels that have already been published as part of the Fragments of the World tetralogy planned by Hélène Rioux are composed of chapters that could, in principle, constitute separate short stories or novellas on their own. However, each novel in the series allows the reader to note the relationship between the characters and places. The author shows the inhabitants of the Earth during only one day in each novel: an equinoxor a solstice. For the writer and her fictional alter ego, the rhythm of creation is determined by the movement of the Earth around the Sun. Even though Rioux’s characters live in diverse places and in different ways, they are very much alike when faced with the everyday escape from the routine or succumbing to modern rituals. Key words: Hélène Rioux, Fragments of the World, rituals, rhythm, routine